Rat in vitro spermatogenesis promoted by chemical supplementations and oxygen-tension control - Takafumi Matsumura (Nature Portfolio, 2021)
Abstract In vitro spermatogenesis (IVS) using air–liquid interphase organ culture method is possible with mouse testis tissues. The same method, however, has been hardly applicable to animals other than mice, only producing no or limited progression of spermatogenesis. In the present study, we challenged IVS of rats with modifications of culture medium, by supplementing chemical substances, including hormones, antioxidants, and lysophospholipids. In addition, reducing oxygen tension by placing tissues in an incubator of lower oxygen concentration and/or applying silicone cover ceiling on top of the tissue were effective for improving the spermatogenic efficiency. Through these modifications of the culture condition, rat spermatogenesis up to round spermatids was maintained over 70 days in the cultured tissue. Present results demonstrated a significant progress in rat IVS, revealing conditions commonly favorable for mice and rats as well as finding rat-specific optimizations. This is an important step towards successful IVS in many animal species, including humans.